The Reunion of the Episcopal Church, 1865 - Shanks, Henry T. (Church history, 1940)
When the American Civil War began, the Southern dioceses of the Protestant Episcopal Church organized a Confederate Church. Contrary to sentiment in the other popular Protestant denominations, there was in 1861 little hostility between the Confederate and Northern leaders of this Church. As the war progressed, however, bitterness developed until in 1865 at the close of the war many wanted to retain separate church organizations. Despite these animosities, some bold spirits succeeded in bringing about the reconciliation of the dioceses of the Church. The story of this reunion has been told before, but new material recently made available warrants a new analysis.